THE INFLUENCE OF LIQUIDITY, LEVERAGE, AUDIT TENURE, AUDITOR'S REPUTATION AND COMPANY GROWTH ON GOING ON CONCERN OPINION: Case Study of Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the 2019 - 2021 Period - Novita Sari Br Sianturi; Togiana Situmorang; Yois Nelsari Malau; Wenny Anggeresia Ginting (Journal Accounting International Mount Hope, 2024)
The purpose of this research is to determine the influence of Liquidity, Leverage, Audit Tenure, Auditor Reputation and Company Growth on Going on Concern Opinions in Property and Real Estate Companies Listed on the Indonesian Stock Exchange for the 2019 - 2021 Period. Research from June 2022 to April 2023. This approach uses a quantitative approach. The population used is 77 property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2022. Sampling used the purpose sampling method. The results of this research indicate that Liquidity, Audit Tenure, Auditor Reputation and Company Growth do not have a partially significant influence on Going on Concern Opinion. There is a partially significant influence between Leverage on Going on Concern Opinion. Liquidity, Leverage, Audit Tenure, Auditor Reputation and Company Growth do not have a significant effect on Going on Concern Opinion.